A low profile metasurface‐based circularly polarized antenna. Issue 3 (13th December 2021) - Zhang, Yamei; Xu, Feng
Abstract: A wideband circularly polarized antenna with low profile based on metasurface is proposed in this article. The antenna is excited by a wideband phase shifter with four output ports. We use a wideband single‐ended‐to‐balanced power divider; the wideband is achieved by microstrip‐to‐slotline transitions and a slotted T‐junction. The slotlines on the ground act as multimode resonators and provide one resonator pole in operating band. We use composite right/left‐handed to obtain stable phase difference at four output ports. Sequential rotation technology is used to realize wideband circularly polarized performance, the metasurface arrays is used to further improve the bandwidth. The whole structure is composed of two substrates and the two substrates are connected with metal pillars. The wideband circularly polarized antenna is designed, fabricated, and measured. The measured results show that the 37.4% impedance matching is obtained, ranging from 5 to 7.3 GHz. And the 3 dB axial ratio fractional bandwidth is 31.8%, ranging from 5.25 to 7.15 GHz. The maximum measured gain is 10.24 dBi, showing good agreement with the simulated results.